Réponses

  • Utilisateur Brainly
2014-03-18T18:55:25+01:00
1/ (x+1):3 - (x-1):4= x:2 - (x-2):12
4(x+1)-3(x-1)=6x-(x-2)
4x+4-3x+3=6x-x+2
x+7=5x+2
4x=5
x=0,8

 2/ x:2 -5= x:3+1
3x-30=2x+6
x=36
2014-03-18T18:59:00+01:00

Résoudre ces équations sans oublier les étapes et non le résultat seul :

1)
(x + 1) : 3 - (x - 1) : 4 = x : 2 - (x - 2) : 12
4 (x + 1) - 3 (x -1) = 6x - (x - 2)
4x + 4 - 3x + 3 = 6x - x + 2
x + 7 = 5x + 2
4x = 5
x = 5/4
x = 1,25

2/x : 2 - 5 = x : 3 + 1
3x - 30 = 2x + 6
3x - 2x = 30 + 6
x = 36